Guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants. Issue 2 (25th January 2021) - Rangecroft, Sally; Rohse, Melanie; Banks, Eddie W.; Day, Rosie; Di Baldassarre, Giuliano; Frommen, Theresa; Hayashi, Yasunori; Höllermann, Britta; Lebek, Karen; Mondino, Elena; Rusca, Maria; Wens, Marthe; et al.
ABSTRACT: To explore and address complex water-related issues, true collaborative, interdisciplinary research at the interface of hydrology and social science is necessary. Accordingly, hydrologists are increasingly working with social sciences and becoming involved in fieldwork with participants. With the overarching aim of facilitating collaboration and interdisciplinary water research, here we discuss important considerations and guiding principles for hydrologists, both those new to and those already familiar with interdisciplinary research, who are: (i) involved in fieldwork with participants; and (ii) working more collaboratively with social scientists. Drawing on first-hand experiences, this paper combines theory and experience from hydrologists and social scientists from their various interdisciplinary research projects to better understand key ethical, theoretical and practical considerations when working with participants. Complementary to this, we discuss the barriers and opportunities in collaborative interdisciplinary research. Facilitating these practices and understandings for hydrologists is essential to strengthen collaboration and to develop more holistic, successful research.